Magnesium isotopic systematics of the Makran arc magmas, Iran: Implications for crust-mantle Mg isotopic balance. (1st June 2020) - Pang, Kwan-Nang; Teng, Fang-Zhen; Sun, Yang; Chung, Sun-Lin; Zarrinkoub, Mohammad Hossein
Abstract: Continental crust loses Mg by lower crustal foundering and chemical weathering to become its intermediate-silicic composition. Both processes should preferentially retain heavy Mg isotopes in the crust, yet the estimated Mg isotopic ratio for the bulk continental crust is indistinguishable from that for unmodified mantle. This can be elucidated by two notions that are not mutually exclusive: (i) the basaltic parent to the crust has Mg isotopes lighter than the mantle and has since become mantle-like as a result of Mg loss by igneous and weathering fractionation, and (ii) heavy Mg isotopes in the continental crust are constantly balanced by a hidden input of light Mg isotopes. Arc magmas are arguably building blocks of the continental crust and their Mg isotopic signature could be used to place limits on the above views. Here, we conducted a Mg isotopic study of the Makran arc, a rare continental arc in Iran within the Alpine-Himalayan orogenic belt. The measured Mg isotopic ratios for most mafic and intermediate samples are mantle-like with δ 26 Mg values ranging from −0.32‰ to −0.20‰. After excluding dubious samples affected by alteration, the silicic samples span a broad range of isotopic ratios with δ 26 Mg values ranging from −0.32‰ to +0.32‰, beyond that of unmodified mantle (δ 26 Mg = −0.25 ± 0.04‰). The isotopic data form a trend from mantle-like δ 26 Mg at relatively high MgO towards elevated δ 26 Mg at low MgO, requiring the isotopic variability be related to differentiation in an open system involving assimilation of high-δ 26 Mg crustal rocks. Our results are generally consistent with Mg isotopic data compiled for global arcs where magmas have Mg isotopic ratios ranging from mantle-like to ∼0.7 per mil above the mantle range, and compositions substantially below that range are rare. Thus, heavy Mg isotopes in the continents predicted by igneous and weathering fractionation might have been compensated by a hidden input of light Mg isotopes, which is presumably in the form of carbonates, leading to a bulk crustal Mg isotopic composition that is mantle-like.